2020
DOI: 10.1002/pca.2970
|View full text |Cite
|
Sign up to set email alerts
|

TLC–MS identification of alkaloids in Leonuri Herba and Leonuri Fructus aided by a newly developed universal derivatisation reagent optimised by the response surface method

Abstract: Introduction Dragendorff's reagent has low sensitivity and non‐specificity for some alkaloids. A new alkaloid derivatisation reagent has been developed and optimised by using a Box–Behnken design method. This new reagent is applicable for structurally diverse natural alkaloids, and is proposed as a universal alkaloid staining reagent. Objective To establish an efficient and sensitive thin‐layer chromatography (TLC) identification method for Leonuri Herba and Leonuri Fructus to characterise their differences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Compound 1 was isolated as a pink amorphous powder, with a positive result to Dragendorff’s reagent (orange red), indicating the presence of an alkaloid skeleton. , HRESIMS and 13 C NMR (Table ) analyses revealed a molecular formula of C 39 H 44 N 2 O 6 at m / z 637.3269 [M + H] + (calcd for C 39 H 45 N 2 O 6 , 637.3272). The 1 H NMR spectrum (Table ) revealed two N -methyl signals at δ H 2.84 and 2.87, four aromatic proton singlets at δ H 6.88, 6.81, 6.53, and 6.00, corresponding to two 1,2,4,5-tetra-substituted aromatic rings, a pair of doublets at δ H 6.73 (2H, d, J = 8.4 Hz) and 6.96 (2H, d, J = 8.3 Hz) of an AA′BB′ system, and an ABX system with δ H 6.33 (1H, d, J = 1.9 Hz), 6.75 (1H, d, J = 8.4 Hz), and 6.78 (1H, dd, J = 8.3, 1.9 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…Compound 1 was isolated as a pink amorphous powder, with a positive result to Dragendorff’s reagent (orange red), indicating the presence of an alkaloid skeleton. , HRESIMS and 13 C NMR (Table ) analyses revealed a molecular formula of C 39 H 44 N 2 O 6 at m / z 637.3269 [M + H] + (calcd for C 39 H 45 N 2 O 6 , 637.3272). The 1 H NMR spectrum (Table ) revealed two N -methyl signals at δ H 2.84 and 2.87, four aromatic proton singlets at δ H 6.88, 6.81, 6.53, and 6.00, corresponding to two 1,2,4,5-tetra-substituted aromatic rings, a pair of doublets at δ H 6.73 (2H, d, J = 8.4 Hz) and 6.96 (2H, d, J = 8.3 Hz) of an AA′BB′ system, and an ABX system with δ H 6.33 (1H, d, J = 1.9 Hz), 6.75 (1H, d, J = 8.4 Hz), and 6.78 (1H, dd, J = 8.3, 1.9 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, two chromogenic reagents Dragendorff's and Wagner were used for the color reaction of most alkaloids, while they present poor effects for some alkaloids with small molecular weight. Considering acidic environment should be provided for the color reaction, the acetic acid was replaced as phosphoric acid in Dragendorff's reagent for improving the chromogenic sensitivity, referring what Zhang N, et al reported [72]. Moreover, if the color of spots is red, such as orange red or brownish red, the compounds represented by the spots are likely not choline analogs, while are likely alkaloids, possibly some polymethoxy flavonoids, or polymethoxybenzenes (such as α-and β-asarones) since the potassium bismuth iodide reagent colors these compounds to orange red or brownish red.…”
Section: A Simple Methods Detecting Choline Analogs From Plant Resourcementioning
confidence: 99%
“…The presence of alkaloids was detected by Wagner's or Dragendorff's reagents [27], which produce a golden-brown-or reddish-brown-colored reaction in response to alkaloids, respectively (the intensity of staining depends on the quantity of alkaloids). Wagner's reagent (iodine potassium iodide solution) was prepared by dissolving 2 g I 2 and 6 g KI in 100 mL of distilled water.…”
Section: Determination Of Alkaloidsmentioning
confidence: 99%